The Impact and Feasibility of Introducing Height-Adjustable Desks on Adolescents’ Sitting in a Secondary School Classroom - Rick Baldock; Bernie Holland; Bronwyn Sudholz; Anna Timperio; Nicola D. Ridgers; Jo Salmon; David W. Dunstan (AIMS Public Health, 2016)
Children spend over 60% of their school day sitting; much of this occurs in the classroom. Emerging research has examined the impact of environmental interventions on classroom sitting. While this research is promising, it has predominantly focused on the primary school setting. This study examined the impact and feasibility of height-adjustable desks on time spent sitting/standing during classroom lessons in a secondary school. Traditional desks in a Melbourne secondary school classroom were replaced with 27 height-adjustable desks (intervention classroom). Forty-three adolescents (51% male; mean age 13.7 ± 1.4 years) from Grades 7, 9 and 10 wore an inclinometer and accelerometer for schooldays and completed a survey after using the desks during lessons for seven weeks. Ten teachers (50% male) completed a survey. Time spent sitting, standing, and the length of sitting bouts were compared between periods when adolescents were in the intervention classroom versus traditional classrooms (matched on teacher and subject). Compared to the traditional classroom, adolescents spent 25% less time sitting and 24% more time standing in the intervention classroom (effect size > 0.8), and had a greater frequency of short sitting bouts and fewer longer bouts. The majority of teachers (71%) and students (70%) reported wanting to continue to use the height-adjustable desks. When standing during lessons, adolescents reported working well (69%); however, a third reported difficulties paying attention (28%) and becoming distracted (36%). Few teachers reported negative influences on adolescents’ ability to work (14%) and concentrate (14%). Half the adolescents reported leg, or back pain with standing. Introducing height-adjustable desks resulted in lower levels of sitting compared with traditional classrooms, was acceptable and had some adverse effects on concentration and discomfort. The study provides preliminary evidence that height-adjustable desks may help reduce prolonged sitting in school among adolescents. Future research should incorporate a control group and explore behavioural and academic outcomes.